2017
DOI: 10.1016/j.bbmt.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance versus Induction Therapy Choice on Outcomes after Autologous Transplantation for Multiple Myeloma

Abstract: Bortezomib (V), lenalidomide (R), cyclophosphamide (C) and dexamethasone (D) are components of the most commonly used modern doublet (RD, VD) or triplet (VRD, CVD) initial induction regimens prior to autologous hematopoietic cell transplantation (AHCT) for multiple myeloma (MM) in the US. In this study we evaluated 693 patients receiving “upfront” AHCT after initial induction therapy with modern doublet or triplet regimens using data reported to the Center for International Blood and Marrow Transplant Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(67 citation statements)
references
References 34 publications
0
67
0
Order By: Relevance
“…PFS was significantly better in the LEN(+) group, although the groups were small, and only 53% of patients in the LEN(+) group received LEN maintenance as a part of the Phase 2 study. A recent study suggested that post‐transplant maintenance was more important than the type of induction regimen used in patients with MM . In our study, patients who received LEN‐based induction and LEN maintenance did not have significantly better PFS compared with those who did not receive maintenance, although the groups were very small.…”
Section: Discussionmentioning
confidence: 49%
“…PFS was significantly better in the LEN(+) group, although the groups were small, and only 53% of patients in the LEN(+) group received LEN maintenance as a part of the Phase 2 study. A recent study suggested that post‐transplant maintenance was more important than the type of induction regimen used in patients with MM . In our study, patients who received LEN‐based induction and LEN maintenance did not have significantly better PFS compared with those who did not receive maintenance, although the groups were very small.…”
Section: Discussionmentioning
confidence: 49%
“…However, the effect on OS rates was not statistically significant ( P = 0.485), which may be associated with fewer cases in the traditional regimen. Moreover, some researchers have considered that the consolidation and maintenance therapy after transplantation is especially important for the long‐term survival of patients who have not reached CR after transplantation . It is noteworthy that in the present study, 1 patient was in PR after 3 recurrences following traditional drug chemotherapy before transplantation.…”
Section: Discussionmentioning
confidence: 52%
“…Age, line of therapy at bortezomib initiation, baseline renal function, disease stage, and depth of best response appeared prognostic for PFS and OS in this study; several of these parameters have also been identified as prognostic for outcomes in the clinical trial setting . Of note, the distributions of PFS or OS when stratified by best response were not markedly affected by response criteria.…”
Section: Discussionmentioning
confidence: 99%